Little Black Daydream - Kistulentz, Steve (Book collections on Project MUSE., 2013)
Steve Kistulentz?s second book of poems, Little Black Daydream, is a chronicle of post-capitalist America. With a precise ear for the American patois, it addresses the uncertainty of the future at the exact moment when those questions are at the forefront of our culture. The book teems with the dazzling detritus of desire, capitalism, and apocalypse-and the poems demonstrate an astonishing adeptness at pushing language to portray this strange moment in our histories, both the personal and the fantastical.?-Carmen Gimnez Smith, author of The City She Was and Odalisque in Pieces.